Challenging the Hegemony of the Symptom: Reclaiming Context in PTSD and Moral Injury. Issue 6 (31st October 2020) - Kinghorn, Warren
Abstract: Although post-traumatic stress disorder (PTSD) is now constituted by a set of characteristic symptoms, its roots lie in Post-Vietnam Syndrome, a label generated by a Vietnam-era advocacy movement that focused not on symptoms but on war's traumatic context. When Post-Vietnam Syndrome was subsumed into the abstract, individualistic, symptom-centered language of DSM-III and rendered as PTSD, it not only lost this focus on context but also neglected the experiences of veterans who suffer from things done or witnessed, not primarily from what was done to them, in war. This agent-related trauma has been rediscovered in contemporary work on moral injury, but moral injury too is increasingly subjected to the hegemony of the symptom. Focusing on symptoms, however, unhelpfully pathologizes and individualizes trauma, neglects traumatic context, and legitimates problematic therapeutic approaches. Trauma researchers and clinicians should decenter the language of symptoms and focus instead on context and on alternative accounts of trauma.